Regeneration of the dermal skeleton and wound epidermis formation depend on BMP signaling in the caudal fin of platyfish - Rees, Lana; König, Désirée; Jaźwińska, Anna (Frontiers in Cell and Developmental Biology, 2023)
Fin regeneration has been extensively studied in zebrafish, a genetic model organism. Little is known about regulators of this process in distant fish taxa, such as the Poeciliidae family, represented by the platyfish. Here, we used this species to investigate the plasticity of ray branching morphogenesis following either straight amputation or excision of ray triplets. This approach revealed that ray branching can be conditionally shifted to a more distal position, suggesting non-autonomous regulation of bone patterning. To gain molecular insights into regeneration of fin-specific dermal skeleton elements, actinotrichia and lepidotrichia, we localized expression of the actinodin genes and bmp2 in the regenerative outgrowth. Blocking of the BMP type-I receptor suppressed phospho-Smad1/5 immunoreactivity, and impaired fin regeneration after blastema formation. The resulting phenotype was characterized by the absence of bone and actinotrichia restoration. In addition, the wound epidermis displayed extensive thickening. This malformation was associated with expanded Tp63 expression from the basal epithelium towards more superficial layers, suggesting abnormal tissue differentiation. Our data add to the increasing evidence for the integrative role of BMP signaling in epidermal and skeletal tissue formation during fin regeneration. This expands our understanding of common mechanisms guiding appendage restoration in diverse clades of teleosts.